Therapeutic Management of Notoedric Mange in Cat - dangi, Rakesh; Mehta, Hemant Kumar; Choudhary, Nidhi S.; Agrawal, Vivek; Singh, Tanya; Bhagherwal, Rajendra (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
A young Persian male cat was presented to Veterinary Clinical Complex, CoVSc & A.H. MHOW (M.P.) with history of crust formation, hyperkeratosis, alopecia, and intense pruritus. Lesions were found on the ear margins, the face, and the legs. The sample was found positive for Notoedres cati (feline scabies) by examination of skin scrapping using 10% KOH solution. Morphological observations viz. round body, short legs, and a dorsal anus, confirmed the infestation. The infected cat was treated with spot-on containing combination of Fipronil 74.4 mg, (S)- methoprene 90.0 mg, eprinomectin 3.60 mg, and praziquantel 74.7mg, twice at 28 days interval, oral administration of enrofloxacin @ 5mg/kg b.wt. for 7 days, and coat supplement containing Omega fatty acids for 15 days. The cat completely recovered after 48 days of treatment.